RUPA DAN MAKNA SIMBOLIS BATIK MOTIF MODANG, CEMUKIRAN - Aan Sudarwanto (Pascasarjana Institut Seni Indonesia Surakarta, 2012)
This article presents and identifies the formand symbolicmeaning of the batikmotif known asmodang, cemukiran. Thepresentation beginswith an explanation of the formof the batikmotifmodang, cemukiran, followed by an interpretationof the symbols surrounding it. The symbols are interesting in that a single symbol can explain a dual function, namely atranscendent-vertical function (related to reference, size, and the behavioural patterns of the community) and an immanenthorizontalfunction (as a means of communication based on its context and close connection with the solidarity of thesupporting community). In order to discovermore about the symbols surrounding the batikmotifmodang, cemukiran, itis first necessary to learn about the background of the personwho designed thismotif. Based on the nature of thought of theJavanese with regard to sacred symbols,which are constantly used as guidelines in every aspect of their lives, themodangand cemukiranmotif can be understood to be a symbol of flames.Modang and cemukiran aremotifswhich have certainsimilarities from the point of view of their visual form. The modang motif can be said to be a form of stylization of thearrangement or organization of the shape of firewhich has a flexible nature. Based on this analysis, the shape of the fire canbe said to be closer to its real form, whereas the shape of the cemukiranmotif ismore of a deformation of shape; that is, anornamentation created by breaking down and then rearranging the shape to achieve the desired form. In itsmanifestation, fireis elaborated in the formofmodang and cemukiranmotifs,whose application appears on batik cloth, the decorative plating onthe sheath of a traditional dagger or keris, and a number of ornaments on the interior of the palace or keraton.Keywords: Symbol,Modang,Cemukiran, FlamesÂ